2001
DOI: 10.1521/scpq.16.1.56.19157
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between training type and treatment integrity.

Abstract: In recent years there has been a renewed interest in the assessment of treatment integrity. Current studies have examined means by which to increase treatment integrity but may be limited by an overreliance on indirect measures of treatment integrity and failure to address multiple training methods within one study. The present study was conducted to investigate the relationship between training procedures and treatment integrity. Participants first read a case description and intervention plan for a client (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…Whereas some investigators have suggested a positive relationship between acceptability and treatment integrity (Allinder & Oats, 1997), others have found none to exist (Peterson & McConnell, 1996;Sterling-Turner & Watson, 2002). In summary, the existing literature suggests an unclear relationship between these constructs.…”
Section: Treatment Acceptabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…Whereas some investigators have suggested a positive relationship between acceptability and treatment integrity (Allinder & Oats, 1997), others have found none to exist (Peterson & McConnell, 1996;Sterling-Turner & Watson, 2002). In summary, the existing literature suggests an unclear relationship between these constructs.…”
Section: Treatment Acceptabilitymentioning
confidence: 86%
“…Given that some alterations are expected, it seems obvious that we make it a priority to identify the critical components of an innovation (Schoenwald & Hoagwood, 2001). A number of researchers have observed that some components of a treatment may have a greater impact on outcomes than others (Gansle & McMahon, 1997;Noell, Gresham, & Gansle, 2002;Sterling-Turner & Watson, 2002).…”
Section: Building Usable Knowledgementioning
confidence: 99%
“…Although it is assumed that some treatments may be at higher risk for inaccuracies, treatment integrity data have not been reported for studies with more or less complex interventions. It is recommended that treatment integrity be collected on a number of interventions to determine whether complexity of treatments or other features of the treatment (e.g., acceptability; Sterling-Turner & Watson, 2002) Kelly's (1977) definition of risk that he developed based on reviewing reliability reporting trends in JABA. This conceptualization of risk for independent variable inaccuracies does not include treatment agent (e.g., certified behavior analyst vs. novice therapist), years of experience, setting, or other variables that may be germane to our consideration of risk.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
“…A number of studies have been published in recent years that have examined variables associated with adequate treatment integrity (DiGennaro, Martens, & Kleinmann, 2007;DiGennaro, Martens, & McIntyre, 2005;Mortenson & Witt, 1998;Noell, Witt, Gilbertson, Ranier, & Freeland, 1997;Noell et al, 2000;Sterling-Turner, Watson, Wildmon, Watkins, & Little, 2001;Witt, Noell, LaFleur, & Mortenson, 1997). Most of these studies have focused on schools as the primary setting for investigation.…”
mentioning
confidence: 99%
“…Because all of these factors are important, treatment acceptability, which encompasses many of the mentioned variables, is considered to be critical in influencing treatment integrity and intervention success. More specifically, research suggests that there is a relationship between integrity and acceptability of behavioral interventions (Lentz et al, 1996;Sterling-Turner & Watson, 2002); however, little is known about this relationship with respect to academic interventions, particularly when the interventions are used with children with ADHD.…”
mentioning
confidence: 99%